EDUCATION FOR COMMUNITY IN EFFORTS TO PREVENT DRUG USED IN SEI PANGERAN KECAMATAN ILIR TIMUR I PALEMBANG - Ridwan, Ridwan; Shobur, Sherli; Sulaiman, Sulaiman (Universitas Muhammadiyah Tapanuli Selatan, 2021)
Background, Drugs can damage human health both physically, emotionally and the behavior of the user. an increase in drug trafficking during 2019 from the previous year of 0.03 percent. Most users are aged 15 to 65 years and exceed the three million people. more than 4 million Indonesians are drug users. The prevalence of abuse among students and college students is 3.21 percent or the equivalent of 2 million students who have abused drugs in 2018. Meanwhile, drug use among workers is 2.1 percent or more than 1.5 million people. So drugs are not only in Indonesia yes, around the world it's about the same. But in Indonesia we have increased by 0.03 percent. Approximately 3,600,000 people use this in Indonesia,